Secular conversions: political institutions and religious education in the United States and Australia, 1800-2000 - Mayrl, Damon (Cambridge studies in social theory, religion and politics, 2016)
Politics, institutions, and secularization -- Forging the nineteenth-century settlement, 1800-1880 -- State-building and secularization in comparative perspective -- The nineteenth-century settlement in transition, 1880-1945 -- Slow secularization in the permeable American state -- Settlement stability in the insulated Australian state -- Forging the twentieth-century settlement, 1945-2000 -- Secularization and the courts in postwar America -- Desecularization and electoral institutions in postwar Australia -- Implications -- Toward a twenty-first century settlement?